Measuring Metabolism by Indirect Calorimetry - Kravchychyn, Ana Claudia Pelissari (2010)
Due to its prophylactic and therapeutic importance, dietary behavior has been the object of research in several health areas. Effective treatments for different cases require reliable and individualized daily energy requirements. Indirect calorimetry measures energy expenditure by an analysis of gas exchange in the body. Current review shows the method’s clinical applications. After being organized and analyzed, the above-mentioned studies revealed that indirect calorimetry provides important information on the dietary behavior of different groups. Since the method may be used in clinical and surgical treatments and in athletic performance, its importance for nutritional diagnosis is highlighted.